HRM and work practices in Chile: the regulatory power of organisational culture. Issue 3 (3rd April 2017) - Rodriguez, Jenny K.; Stewart, Paul
Abstract : Purpose: The purpose of this paper is to provide insight into the characteristics of working practices, in particular HRM practices in work settings in Chile, specifically the regulatory strength of organisational culture. Design/methodology/approach: The paper is based on data gathered from a non-probabilistic sample of 1299 workers in the Metropolitan Region of Chile. Findings: Findings suggest that HRM practices sustain, while restructuring, dynamics of worker monitoring and control, consistent with historical and social patterns of relationships in Chile. These relationships are sustained via status differences and operate through the development of paternalistic relationships between managers and workers. Originality/value: The paper provides insight into the character of human resource management in Latin America from the perspective of workers. In addition, it highlights the impact of organisational culture on regulating workplaces and shaping HRM practices that do not challenge the socio-cultural order.